2019
DOI: 10.1002/ecy.2615
|View full text |Cite
|
Sign up to set email alerts
|

Moderate fire severity is best for the diversity of most of the pollinator guilds in Mediterranean pine forests

Abstract: Fire, a frequent disturbance in the Mediterranean, affects pollinator communities. We explored the response of major pollinator guilds to fire severity, across a fire‐severity gradient at different spatial scales. We show that the abundance of all pollinator groups responded to fire severity, and that bees and beetles showed in addition a significant species‐diversity response. Bees, sawflies, and wasps responded to fire severity at relatively small spatial scales (250–300 m), whereas flies and beetles respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 79 publications
(184 reference statements)
3
52
0
1
Order By: Relevance
“…Thus, our review also evidences gaps in the current knowledge (Figure ). Our synthesis was not able to include the effect of important spatial factors like fire size (García et al, , ) and the spatial heterogeneity of fire regime parameters (Brown & York, ; Lazarina et al, ; Ponisio et al, ), which are highly related to the mobility of the animals and their landscape scale persistence (Pausas, ). There are not enough studies that analyse the spatial component of the fire regime to be able to perform a global meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our review also evidences gaps in the current knowledge (Figure ). Our synthesis was not able to include the effect of important spatial factors like fire size (García et al, , ) and the spatial heterogeneity of fire regime parameters (Brown & York, ; Lazarina et al, ; Ponisio et al, ), which are highly related to the mobility of the animals and their landscape scale persistence (Pausas, ). There are not enough studies that analyse the spatial component of the fire regime to be able to perform a global meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The IDH has been well supported for fire‐prone vegetation (Dee & Menges, ; Gordijn, Everson & O'Connor, ; Fig. C) but there has been little relevant work done on animals (Lazarina et al, ). If the species trajectories we have outlined above hold generally, it follows that the model must apply to fire‐prone systems generally.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 98%
“…By contrast, other recent studies have found bee diversity to be greatest in moderate burn severities in Mediterranean pine forests (Lazarina et al, 2019) or in high-severity burns for douglas fir-dominated forests in Oregon (Galbraith et al, 2019), or to not differ between mixed-and high-severity burns for several forest types across Montana (LaManna et al, in review). One potential explanation in this discrepancy across studies is the interactive effects of burn severity and time-since-burn; that is, the effects of burn severity can vary in both direction and magnitude across successional time.…”
Section: Discussionmentioning
confidence: 86%
“…For example, bee diversity has been observed to increase with greater pyrodiversity in mixed‐conifer forest in the Sierra Nevadas (Ponisio et al, ) and bee richness has been observed to be greater in mixed‐ compared to high‐severity burns in this system (Simanonok, ); however, that finding was based on a larger range of bee species whereas this manuscript only focuses on a specific nesting guild. By contrast, other recent studies have found bee diversity to be greatest in moderate burn severities in Mediterranean pine forests (Lazarina et al, ) or in high‐severity burns for douglas fir‐dominated forests in Oregon (Galbraith et al, ), or to not differ between mixed‐ and high‐severity burns for several forest types across Montana (LaManna et al, in review). One potential explanation in this discrepancy across studies is the interactive effects of burn severity and time‐since‐burn; that is, the effects of burn severity can vary in both direction and magnitude across successional time.…”
Section: Discussionmentioning
confidence: 86%